‘Keep your private stuff private!’: mitigating young people’s intimate exchanges online - Spišák Sanna (Taylor & Francis, 2022)
This article explores Finnish regulatory authorities’ attempts to mitigate young people’s participation in mediated sexuality. Previous studies have argued that both attempted regulation and education about media and sexuality are often out of touch with many adolescents’ lives. This study uses a Foucauldian inspired critical investigative method to unpack the pedagogical messages that frame official statements and the approaches used by Finnish authorities to regulate mediated sexual exchanges. Focusing on the uses of shame as an ongoing pedagogical strategy, the article reveals the limits of social policing. It also sheds light on alternative possibilities and their implications for different aspects of mediated sexuality (autonomy, privacy and consent among other things) that are currently effaced by the regulatory discourse deployed by the Finnish Police Force.